Comparison of prophylactic dexmedetomidine and ketamine for the control of shivering under spinal anaesthesia - Murmu, Rituparna; Das, Amartya; Roychoudhury, Swarupa (International Journal of Advances in Medicine, 2021)
Background: Shivering is a common problem during neuraxial block. Thermoregulatory control gets compromised by neyraxial block and as a result the incidence of shivering can go up to 56.7%. Aim of the current investigation was to evaluate the effectiveness of prophylactic use of intravenous dexmedetomidine and ketamine for the control of shivering and to note any side-effects of the drugs used during subarachnoid block. Methods: This randomised single blind study was conducted in 151 ASA grade I and II patients. SAB was performed with 3.0mL (15 mg) of 0.5% bupivacaine heavy in all patients. Patients were randomly allocated into two groups of 75 and 76each to receive dexmedetomidine (0.5 µg/kg) in group D and ketamine (0.5 mg/kg) in group K respectively. Temperature and hemodynamic parameters were recorded at every 15mins interval. Shivering was graded from 0 to 4 according to Tsai and Chu and if grade 3 shivering occurred, the study was stopped and pethidine 25 mg was given intravenously as rescue drug. Results: 2.67% of patients in group D had shivering whereas 38.16% patients in group K experienced shivering at the 5th minute after spinal anaesthesia and it was statistically significant. However the difference in the incidence of shivering was not statistically significant between the two groups after the initial 5 minutes till the end of surgery. Conclusions: The prophylactic use of dexmedetomidine reduced incidences of shivering more effectively as compared to prophylactic use of ketamine. None of the drugs caused any untoward side effects.